Protection of information from unauthorized access in the design of automated systems radionuclide spectrometry for civil engineering - P. Mikhnev, Ilya; A. Salnikova, Natalia; V. Mikhneva, Svetlana (International Journal of Engineering and Technology, 2019)
Designing protection systems involves developing a protection model and transferring it to a specific software structure. The security model is a description, formalized or not, of the rules for the interaction of resources in the software-hardware environment of automated systems. Protection models allow you to focus on the most important aspects of the problem of protecting information, discarding the technical details of the system from consideration. The article presents research of information security tools against unauthorized access of automated radionuclide spectrometry systems based on a scintillation gamma spectrometer. As a result of the conducted research, the indicators of the system security were obtained, which allow to calculate and optimize the probability of damage from unauthorized access, taking into account the time of operation and the information security tools used. The developed analytical assessments make it possible at the design stages of automated systems to calculate the upper and lower bounds of the probability of unauthorized access to confidential information.Â Â